Analisis Kinerja BAZNAS Kota Bengkulu dengan Metode Indonesia Magnificence Zakat (IMZ) - Idia Joninda Piolita; Asnaini; Herlina Yustati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to find out how the management performance, financial performance, and performance of the utilization program at BAZNAS Bengkulu City during 2021-2022 using the Indonesia Magnificence Zakat (IMZ) measurement method. Indonesia Magnificence Zakat is a non-profit organization empowerment and management consulting institution engaged in training, consulting and mentoring, as well as zakat research and advocacy, this performance measurement method is called Zakat Management Excellence Performance. The type of research used in this study is a qualitative evaluation method. The results of the study on three components in BAZNAS Bengkulu City, namely management performance, financial performance, and quality of utilization programs, show that the performance of BAZNAS Bengkulu City obtained a good score in each performance component based on IMZ measurement. In some performances, they show good value components, but there are also those that show low scores, from these results are averaged so that good scores are obtained.